2014
DOI: 10.1155/2014/178064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Morphology and Composition of Inorganic Fillers in Dental Alginates

Abstract: Energy dispersive X-ray spectroscopy microanalysis (EDX), scanning electron microscopy (SEM), and Archimedes' Principle were used to determine the characteristics of inorganic filler particles in five dental alginates, including Cavex ColorChange (C), Hydrogum 5 (H5), Hydrogum (H), Orthoprint (O), and Jeltrate Plus (JP). The different alginate powders (0.5 mg) were fixed on plastic stubs (n = 5) and sputter coated with carbon for EDX analysis, then coated with gold, and observed using SEM. Volume fractions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Our results are in agreement with those of McCabe et al [20] who suggested that potassium alginate with a concentration of 11-16% was a suitable components for an irreversible hydrocolloid [20]. Moreover, other studies reported that the 15% concentration of potassium alginate was appropriate to formulate an irreversible hydrocolloid impression material [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with those of McCabe et al [20] who suggested that potassium alginate with a concentration of 11-16% was a suitable components for an irreversible hydrocolloid [20]. Moreover, other studies reported that the 15% concentration of potassium alginate was appropriate to formulate an irreversible hydrocolloid impression material [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Badali oni jednak głównie tradycyjne masy alginatowe, co w obliczu własnych i przytoczonych badań wydaje się czynnikiem decydującym o takich wynikach. 16,17 W ocenie własnej autorów niniejszej that such a situation takes place regardless of supplying an external source to provide an increase in humidity to the impression storage environment -the minimum average value of the deviation from the reference scan at 144 hours of the study occurred in the group with a wet towel placed in a double-zipped bag without contact with the impression; however, the difference between this group and the group in which the impression had been placed in the double-zipped bag without any additional sources to potentially increase the humidity was statistically insignificant. [15][16][17] Guiraldo et al examined the existence of variations in the inorganic composition of the filler particles.…”
Section: Dyskusjamentioning
confidence: 99%
“…16,17 W ocenie własnej autorów niniejszej that such a situation takes place regardless of supplying an external source to provide an increase in humidity to the impression storage environment -the minimum average value of the deviation from the reference scan at 144 hours of the study occurred in the group with a wet towel placed in a double-zipped bag without contact with the impression; however, the difference between this group and the group in which the impression had been placed in the double-zipped bag without any additional sources to potentially increase the humidity was statistically insignificant. [15][16][17] Guiraldo et al examined the existence of variations in the inorganic composition of the filler particles. Among five alginate materials that were selected for the study, Hydrogum 5 showed the highest content of inorganic filler (84.85%), therefore for this particular material, the lowest volumetric change is expected to occur.…”
Section: Dyskusjamentioning
confidence: 99%
“…When compared to other elastomeric impression materials, these alginate impressions do not exhibit dimensional stability and cannot accurately recreate finer details or surface details. The influence of the filler size and composition, which typically contain about 7.94-14.59 μm filler size [2,4,5], may be responsible.…”
Section: Introductionmentioning
confidence: 99%